Shortening Dental Arch and Splint Crown in Mini Dental Implant - Azhar, Imam Safari; Agustono, Bambang; Ari, Muhammad Dimas Aditya; Laksono, Harry (Indonesian Journal of Prosthodontic, 2021)
A male patient, 40-years-old, came to Dental Hospital Universitas Airlangga with a complaint to replace the lower right and left teeth that had been extracted 1 year ago with a denture that could not be removed. The patient wants to make dentures to make them more comfortable when chewing. The tooth extraction was performed Â± 1 year ago in the lower left posterior tooth region caused caries. Treatment plan: Implant supported splint crown Based on the existing clinical conditions in patient, we examined the thickness of the existing bone. Then we performed to insert an implant fixture 3.0x10 mm type TS III SA in region 34 and 3.5x10 mm type ET III SA Osstem in region 35. This treatment using one stage surgery with splint crown restoration. Clinical significance of therapy/summary: In this case, patient refused invasive surgical procedure as bone augmentation. Shortening dental arch was chosen due to the loss of the antagonist teeth. Implant supported splint crown can be another solution because itâ€™s able to maintain the long term of mini dental implant especially in the posterior region.